A paisagem cultural da serra Santa Helena - Sonale Karla Cordeiro Santos (2011)
The research project: "A CULTURAL LANDSCAPE IN SERRA SANTA HELENA" works up a plan for identification of cultural heritage, through a case study, by using the concept of contemporary cultural landscape estate. The goal is to understand the dynamics of the cultural landscape of the Serra Santa Helena, in the city of Sete Lagoas, Minas Gerais, so that this cultural estate can be preserved. The search becomes important as it develops a way of research on the specific values and the meaning of a particular place, which is recognized by its surrounding community as their own cultural estate. Unlike the general dynamics of preservation agencies which recognize the universal "cultural values" of a given society. To identify the cultural values of this community a new proposal has been developed as a research tool for the Cultural Landscape's Inventory, which is presented and analyzed. Finally it is concluded that the propositions of administration of cultural landscapes in preservation agencies still have to deal with the fact that the phenomena of urban sprawl, globalization and the amassment of urban and rural landscapes continue to endanger contexts of life and local traditions. Therefore, methodological and conceptual revision as well as technical and instrumental innovation becomes necessary, on the implementation of the administrational instruments of cultural landscape by the preservation agencies.